Detecting Image Brush Editing Using the Discarded Coefficients and Intentions - López Hernández, Fernando Carlos; de-la-Fuente-Valentín, Luis; Sarría, Íñigo (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
This paper describes a quick and simple method to detect brush editing in JPEG images. The novelty of the proposed method is based on detecting the discarded coefficients during the quantization of the image. Another novelty of this paper is the development of a subjective metric named intentions. The method directly analyzes the allegedly tampered image and generates a forgery mask indicating forgery evidence for each image block. The experiments show that our method works especially well in detecting brush strokes, and it works reasonably well with added captions and image splicing. However, the method is less effective detecting copy-moved and blurred regions. This means that our method can effectively contribute to implementing a complete imagetampering detection tool. The editing operations for which our method is less effective can be complemented with methods more adequate to detect them.
Keywords: image; forgery; brush; stroke; caption; IJIMAI